The long‐term population dynamics of common wasps in their native and invaded range. (17th January 2017) - Lester, Philip J.; Haywood, John; Archer, Michael E.; Shortall, Chris R.
Summary: Populations of introduced species are often thought to perform differently, or experience different population dynamics, in their introduced range compared to their native habitat. Differences between habitats in climate, competition or natural enemies may result in populations with varying density dependence and population dynamics. We examined the long‐term population dynamics of the invasive common wasp, Vespula vulgaris, in its native range in England and its invaded range in New Zealand. We used 39 years of wasp density data from four sites in England, and 23 years of data from six sites in New Zealand. Wasp population time series was examined using partial rate correlation functions. Gompertz population models and multivariate autoregressive state‐space (MARSS) models were fitted, incorporating climatic variation. Gompertz models successfully explained 59–66% of the variation in wasp abundance between years. Density dependence in wasp populations appeared to act similarly in both the native and invaded range, with wasp abundance in the previous year as the most important variable in predicting intrinsic rate of increase ( r ). No evidence of cyclic population dynamics was observed. Both the Gompertz and MARSS models highlighted the role of weather conditions in each country as significant predictors of annual wasp abundance. The temporal evolution of wasp populations at all sites was best modelled jointly using a single latent dynamic factor for local trends, with the inclusion of a latent spring weather covariate. That same parsimonious multivariate model structure was optimal in both the native and invaded range. Density dependence is overwhelmingly important in predicting wasp densities and 'wasp years' in both the native and invaded range. Spring weather conditions in both countries have a major influence, probably through their impact on wasp colony initiation and early development. The population dynamics in the native range and invaded range show no evidence of cyclic boom‐and‐bust dynamics. Invasive species may not exhibit different population dynamics despite considerable variation in abundances throughout their distribution. Abstract : Common wasps can be abundant and damaging pests. This study shows that the year‐to‐year variation in wasp numbers is governed by similar factors in the native and introduced range. High numbers in 'wasp years' are due to a lower abundance of wasps in the previous year and ideal spring weather conditions.